GAYA HIDUP HEDONISME DI KALANGAN REMAJA PUTRI (Studi Kasus Komunitas Warung Bumi Ayu, Jalan Gunung Agung, Kota Denpasar) - Purwanti, Ni Putu Ari (Humanis, 2016)
Girls have a public image as a figure of tenderness, simplicity, caring, selflessness, stay home and not affected by a negative thing. But in fact, the girls in the community of  Warung Bumi Ayu (WBA or Bumi Ayu Small Shop) are different. The behavior of girls in this community leads to a lifestyle that represents of hedonism. The hedonism lifestyle led to break of status such as skipped the class, breaking the school's rules, fighting, damaging the infrastructure (vandalism), smoking in the environment or outside of the school environment, the consumption of alcohol and breaking parent’s rules, breaking the law such as gambling, drugs using, free sex, and also illegal street racing.
Keywords: Girls, Life Style, and Hedonism